2021
DOI: 10.32607/actanaturae.11043
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation As an Epigenetic Mechanism in the Development of Multiple Sclerosis

Abstract: The epigenetic mechanisms of gene expression regulation are a group of the key cellular and molecular pathways that lead to inherited alterations in genes activity without changing their coding sequence. DNA methylation at the C5 position of cytosine in CpG dinucleotides is amongst the central epigenetic mechanisms. Currently, the number of studies that are devoted to the identification of methylation patterns specific to multiple sclerosis (MS), a severe chronic autoimmune disease of the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…An increasing number of studies are now focusing on the identification of epigenetic changes that cause long-lasting alterations of gene expression in different cell populations, and, as a consequence, the development of various pathological processes. Recent studies have shown that DNA methylation of various blood components (serum, PBMCs, CD4+ and CD8+ T-lymphocytes, CD19+ B-lymphocytes, CD14+ monocytes) may be involved in the development of MS (reviewed in Kiselev et al 2021). Genome-wide DNA methylation profiling of CD4+ and CD14+ cells, performed in the present work, expands a limited series оf analyses of DNA methylation in different leucocyte populations.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…An increasing number of studies are now focusing on the identification of epigenetic changes that cause long-lasting alterations of gene expression in different cell populations, and, as a consequence, the development of various pathological processes. Recent studies have shown that DNA methylation of various blood components (serum, PBMCs, CD4+ and CD8+ T-lymphocytes, CD19+ B-lymphocytes, CD14+ monocytes) may be involved in the development of MS (reviewed in Kiselev et al 2021). Genome-wide DNA methylation profiling of CD4+ and CD14+ cells, performed in the present work, expands a limited series оf analyses of DNA methylation in different leucocyte populations.…”
Section: Discussionmentioning
confidence: 66%
“…For example, most studies investigated DNA methylation levels in MS groups, which included not only never-treated patients, but also patients who received various immunomodulatory drugs before and/or during blood sampling, despite the fact that drug therapy was shown to affect methylation level in blood cells (Maltby et al, 2018b). In fact, locus HLA is the only genomic region, differential methylation of which has been consistently validated in whole blood and several sorted immune cell types (Kiselev et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to aging, methylation appears to be globally increased in MS [reviewed by (229)], with different methylation profiles between MS phenotypes, higher in PPMS compared to RRMS (230), but slightly higher in RRMS compared to SPMS (231). Lymphocyte signaling, T cell activation and migration were common pathways to RRMS and SPMS methylation profiles, while myeloid cell function and neuronal and neurodegenerative genes and pathways were SPMS-specific (231).…”
Section: Epigeneticsmentioning
confidence: 99%